The Contribution of Early Communication Quality to Low-Income Children's Language Success. (July 2015) - Hirsh-Pasek, Kathy; Adamson, Lauren B.; Bakeman, Roger; Owen, Margaret Tresch; Golinkoff , Roberta Michnick; Pace, Amy; Yust, Paula K. S.; Suma, Katharine
The disparity in the amount and quality of language that low-income children hear relative to their more-affluent peers is often referred to as the 30-million-word gap . Here, we expand the literature about this disparity by reporting the relative contributions of the quality of early parent-child communication and the quantity of language input in 60 low-income families. Including both successful and struggling language learners from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development, we noted wide variation in the quality of nonverbal and verbal interactions (symbol-infused joint engagement, routines and rituals, fluent and connected communication) at 24 months, which accounted for 27% of the variance in expressive language 1 year later. These indicators of quality were considerably more potent predictors of later language ability than was the quantity of mothers' words during the interaction or sensitive parenting. Bridging the word gap requires attention to how caregivers and children establish a communication foundation within low-income families.